Transformasi perkhidmatan perpustakaan melalui lonjakan profesionalisme pustakawan - Masli, Japri Bujang; Bronny , Lawrence Nawe (Persatuan Pustakawan Malaysia, 2010)
Users need libraries more than ever now especially in the presence of excessive information which is brought about by the users’ lack of information skills and time. On the other hand, librarians are also being pressured by a dynamic information environment resulting from rapid ICT developments. Libraries need to undergo a service transformation, especially in Sarawak in order for it to become the state with the highest income in Malaysia in 2030. Thus, librarians need to make a professional shift if changes are to be made in improving the provision of library services to their users.